Indoreonectes telanganaensis, a new species of loach (Teleostei: Nemacheilidae) from the Godavari Basin of India - Prasad, Kante Krishna; Srinivasulu, Chelmala; Srinivasulu, Aditya; Anoop, V.k.; Dahanukar, Neelesh (Zootaxa, 2020)
A new species of hill-stream loach, Indoreonectes telanganaensis, is described from a seasonal tributary of the Godavari River at Maisamma Loddi, within the Kawal Tiger Reserve, Telangana State, India. The new species is distinguished from its congeners by a combination of characters including caudal peduncle as long as deep; eye large, its diameter about one-fifth head length; pectoral fin as long as head; nasal barbel reaching the middle of the eye; dorsal-fin origin on vertical through pelvic-fin origin; and bars on the lateral side of the body well defined and wide. We also provide multivariate morphometric, and DNA analysis based on the mitochondrial cytochrome b gene sequence to support the distinction of the new species.